Mutual fund performance in emerging market: Evidence for China - Shao, Wenting (2015)
This paper evaluates the performance of 110 Chinese equity mutual funds during the period from July of year 2010 to July of year 2015. The three traditional single parameter performance measures from Sharpe, Treynor and Jensen together with the Fama and French three-factor model have been employed to examine whether the mutual funds in China beat the market or not. In addition, the study also tests the stock selection and market timing abilities of Chinese mutual fund managers by using the Treynor-Mazuy model and Henriksson-Merton model. The results of Sharpe ratio and Treynor ratio indicate that the majority of sample funds outperformed the market benchmark while the results form Jensen’s measure and Fama-French model show evidence that Chinese mutual funds were able to earn slight excess return over the market benchmark, but not so significant. As for the stock selection and market timing abilities, both the Treynor-Mazuy model and the Henriksson-Merton model suggest superior stock selection ability of most funds but no evidence indicates Chinese mutual fund managers successfully timed the market as the majority of sample funds timed the market in a wrong direction.